(3GdVeGf GdELJeGYj (B:s (3MeGjI GdeSfjf Hjf GbJUGO GdShb hGdYOGdI GdELJeGYjI GdCQOf fehPLG (B/s - (3GdRYHj, eMeO NGdOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2013)
(3EOGQI GdeNGWQ hGdVYa GdELJeGYj(B- (3Ydi ef JbY eSDhdjI MeGjI GdeSfjf?(B- (3GdYed hGdJbGYO(B- (3GdVeGf GdELJeGYj(B- (3gjcdI GdVeGf GdELJeGYj(B- (3GbJUGO CfXeI GdJbGYO(B- (3JCKjQGJ hJCKQGJ HQfGeL GdJbGYO Ydi GdEbJUGO hGdeLJeY(B- (3GdTjNhNI GdScGfjI hGdVeGf GdELJeGYj(B- (3GdVeGf GdELJeGYj aj GdGQOf(B- (3GdeQcR GdeGdj ddeDSSI(B- (3GdfabGJ GdEOGQjI heTGcd GdEOGQI(B- (3JYOjdGJ bGfhf GdVeGf GdELJeGYj(B- (3eSJbHd GdVeGf GdELJeGYj aj GdGQOf(B- (3GdJhUjGJs
(3GdeQGLY U(B.267s
Keywords: (3GbJUGO GdShbs; (3GdVeGf GdELJeGYjs; (3GdYOGdI GdELJeGYjIs